The Current State of Transformative Learning Theory: A Metatheory - Hoggan, Chad (Phronesis)

(untitled) (Université de Sherbrooke, 2018)
This article presents a perspective on the current state of transformative learning theory. It shows how the literature surrounding transformative learning caused it to evolve into a metatheory. This article then offers a definition of transformative learning as a, as well as three criteria that delimit the learning phenomena that the metatheory encompasses. To illustrate how scholars might evaluate epistemological change in terms of its part in an overall transformation, this article explores how and when epistemological change can be considered transformative.